Incentives for flexible consumption and production on end-user level: Evidence from a German case study and outlook for 2030 - Andreas Dietrich (University of Duisburg-Essen, House of Energy Markets & Finance (HEMF), 2023)
The flexibilization of electricity demand and production becomes increasingly important in energy systems with rising shares of fluctuating renewable electricity production. Power-to-heat and cogeneration units, combined with thermal storages, are considered as promising technologies for the provision of flexibility since they allow for a decoupling of thermal loads, electricity consumption and production. Based on a real-world case study, this paper explores the economic potentials of flexible, spot market-oriented operation for small residential heat pumps, electric storage heaters and medium-sized cogeneration systems from an end-usersÂ' view in Germany. Using numerous models for the determination of heat demands, future spot market prices and unit dispatch, financial incentives in terms of expected cost savings (consumption) and profit increases (production) are derived for the years 2015-2017 as well as for three scenarios in 2030. Results suggest that only those consumers with high electricity demand and sufficient thermal storage capacities may substantially benefit from load shifting. Furthermore, existing remuneration schemes for feed-in and high retail prices for electricity consumption hamper a market-oriented production; maximization of electricity self-consumption is the most profitable operation strategy instead. To unlock flexibility potentials on end-user level, increased market price volatility is needed and policy makers should work towards a design of regulated price components that induces less dilution of market price signals.
Keywords: P48; Q42; Q48; 330; power system flexibilization; demand side management; virtual power plant; CHP; heat pump